2020
DOI: 10.1002/cctc.202001522
|View full text |Cite
|
Sign up to set email alerts
|

Four‐Coordinated Manganese(II) Disilyl Complexes for the Hydrosilylation of Aldehydes and Ketones with 1,1,3,3‐Tetramethyldisiloxane

Abstract: The coordinatively unsaturated manganase(II) bis(supersilyl) complex Mn[Si(SiMe3)3]2(THF)2 (2) was synthesized in one step via the reaction of MnBr2 with two equivalents of KSi(SiMe3)3 in THF. Complex 2 acts as an effective precatalyst for the catalytic hydrosilylation of aldehydes and ketones with 1,1,3,3‐tetramethyldisiloxane (TMDS). The catalytic efficiency can be improved by combining 2 and adamantyl isocyanide (CNAd). The stoichiometric reaction of 2 and two equivalents of CNAd led to the isolation of Mn[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The formation of mid- and late-transition metal-silyl complexes from their alkyl congeners by reaction of PhSiH 3 has been observed previously . Furthermore, we have previously reported the disproportionation of putative hydride complexes via liberation of molecular dihydrogen, when dealing with cobalt complexes with the same 2-iminopyrrolyl ligand. , Specifically, silyl-Mn­(II) complexes have been reported and very recently used as catalysts for the hydrosilylation of aldehydes and ketones . Unfortunately, preparative scale reactions to isolate a silyl-Mn­(II) complex were vain, either from the reaction of complex 2 with PhSiH 3 or via a metathetic exchange reaction of the chloride complex 1 with LiSiH 2 Ph.…”
Section: Resultsmentioning
confidence: 87%
“…The formation of mid- and late-transition metal-silyl complexes from their alkyl congeners by reaction of PhSiH 3 has been observed previously . Furthermore, we have previously reported the disproportionation of putative hydride complexes via liberation of molecular dihydrogen, when dealing with cobalt complexes with the same 2-iminopyrrolyl ligand. , Specifically, silyl-Mn­(II) complexes have been reported and very recently used as catalysts for the hydrosilylation of aldehydes and ketones . Unfortunately, preparative scale reactions to isolate a silyl-Mn­(II) complex were vain, either from the reaction of complex 2 with PhSiH 3 or via a metathetic exchange reaction of the chloride complex 1 with LiSiH 2 Ph.…”
Section: Resultsmentioning
confidence: 87%
“…484 Sunada demonstrated that Mn(hmds) 2 (THF) 2 complex Mn130 could also catalyze the carbonyl hydrosilylation reaction without an external ligand (Table 37, entry 13). 485 Recently, Kundu showed that Mn(I)-complex Mn131 also worked well towards the hydrosilylation reaction, albeit a slightly higher reaction temperature was required (Table 37, entry 14). 486 7.2.2.…”
Section: Hydrosilylation Reactionsmentioning
confidence: 99%
“…Further examples of Mn(II) hydrosilylation of aldehydes and ketones were presented by the groups of Madrahimov [46] and Sunada. [47] The latter managing to utilize TMDS (tetramethyldisiloxane) as the silane source. reduce esters to alcohols as the major product instead of ethers like the Cutler group; however, small amounts of ether (10-20%) could also be detected.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Further examples of Mn(II) hydrosilylation of aldehydes and ketones were presented by the groups of Madrahimov 46 and Sunada. 47 The latter managed to utilize TMDS (tetramethyldisiloxane) as the silane source.…”
Section: Review Synthesismentioning
confidence: 99%